Development of height inequality in Zea mays L. and Panicum capillare L. when grown under stress conditions. - Baloch, A. Hameed; Ahmed, Imtiaz; Ahmed, Saeed; Buzdar, M. Aslam (Hanken, 2013)
Panicum capillare L. (Poaceae) is an annual, dominant weed of cotton, maize and other economically important crops of Lasbela District of Balochistan province of Pakistan. The effect of P. capillare competition on size inequality of well-fertilized and irrigated crop of maize (Zea mays L.) was studied at a local farm of Uthal area of Lasbela District. The traditional method (broadcasting) of seeding of Z. mays was implemented during the present study. Monoculture and mixture plots (1 x 1 m-2) of P. capillare and Z. mays were established with four replicates. The plant heights of weed and crop were measured after 30 days of seeding and recorded every ten day interval till the final harvest (70 days after seeding).